Correlation and co-heritability studies of yield and yield-associating characters in apple (Malus domestica) - SRIVASTAVA, K K; DAS, BISWAJIT; AHMED, N; SINGH, S R; RATHER, J A; BHAT, S K (The Indian Journal of Agricultural Sciences, 2012)
Correlation and co-heritability were studied among 13 applie cultivars. Genotypic and phenotypic variance were maximum for number of fruits/tree during both the years. High PCV and GCV were noted for tree volume and high heritability registered for tree spread and tree volume, whereas high genetic advance noted for number of fruits/plant. High heritability coupled with high genetic advance registered for tree volume, number of fruits/plant, fruit weight, and yield/ tree and trunk girth during both the years. High co-heritability was noted for number of fruits/tree and trunk girth and tree height with trunk girth and tree spread. Number of secondary scaffold and tree volume had high co-heritability with yield/ tree for both the years. Genotypic correlation coefficient for most of the association except tree height with number of primary scaffold and number of secondary scaffold with tree volume and tree spread and tree volume with annual extension growth were registered high.